2013
DOI: 10.1371/journal.pone.0077930
|View full text |Cite|
|
Sign up to set email alerts
|

Secretory Phosphatases Deficient Mutant of Mycobacterium tuberculosis Imparts Protection at the Primary Site of Infection in Guinea Pigs

Abstract: BackgroundThe failure of Mycobacterium bovis Bacille Calmette-Guérin to impart satisfactory protection against adult pulmonary tuberculosis has necessitated the development of more effective TB vaccines. The assumption that the vaccine strain should be antigenically as similar as possible to the disease causing pathogen has led to the evaluation of M.tuberculosis mutants as candidate tuberculosis vaccines.Methods/Principal FindingsIn this study, we have generated a mutant of M.tuberculosis (Mtb∆mms) by disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 49 publications
3
46
0
1
Order By: Relevance
“…It has been described that Mtb bacteria defect in PtpB are not capable of developing latent Mtb infection in Guinea pig ten weeks post inoculation (Chauhan et al, 2013). This report underlines the important role of PtpB in the development of LBTI.…”
supporting
confidence: 53%
“…It has been described that Mtb bacteria defect in PtpB are not capable of developing latent Mtb infection in Guinea pig ten weeks post inoculation (Chauhan et al, 2013). This report underlines the important role of PtpB in the development of LBTI.…”
supporting
confidence: 53%
“…Based on their mechanism of action, mPTP inhibitors would likely have no activity against such organisms. Finally, it is possible that functional deficiency of mPTPA and/or mPTPB may be compensated by alternative Mtb phosphatases, such as SapM 15 . Recently, Chauhan et al generated an Mtb mutant (MtbΔmms) by disrupting the genes encoding PtpA, PtpB and SapM.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Chauhan et al generated an Mtb mutant (MtbΔmms) by disrupting the genes encoding PtpA, PtpB and SapM. After ten weeks of infection, guinea pigs infected with MtbΔmms showed a 4.69 log 10 reduction in lung CFU relative to those infected with the isogenic wild-type strain 15 . This mutant was more attenuated in the guinea pig model of chronic TB relative to an Mtb mutant lacking only PtpB 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that SapM was indispensable for Mtb growth and that the infection with MtbDsapM mutant caused a significant reduction in pathological damage in the host [26]. The same group carried out another study to understand the effect of vaccination with the triple knockout mutant MtbDmptpADmptpBDsapM (MtbDmms) versus BCG on the survival and pathogenesis of Mtb [28]. They reported that the vaccination with MtbDmms mutant restricted the growth of Mtb at primary site of infection quite in comparison to BCG.…”
Section: Sapmmentioning
confidence: 99%